The Role of Judges in Criminal Case Trials as Modification and Reform of Criminal Law - Septatinus Hia; Felianis Ndruru; Zetria Erma (IHSA Institute, 2023)
Judges as modifiers and reformers of law mean that judges act as law inventors (recht vinding), in accordance with cultural values that live in society, especially Five pillars values. The aim of this research is to find out the role of judges as modifiers and law reformers who can be a reference for justice seekers and as jurisprudence for law enforcers. The type of research in this paper is normative with a statutory and conceptual approach. Meanwhile, the specification of this research is analytical descriptive. The data used is secondary data consisting of primary legal materials in the form of the 1945 Constitution, Law no. 48 of 2009 concerning judicial power, and secondary legal materials such as books, journals, and writings related to research titles. The role of judges in deciding criminal cases is expected to fulfill a sense of justice for society. In deciding a case, judges have freedom and power, therefore, apart from paying attention to the provisions written in the law, judges also use instinct, namely based on the judge's beliefs and the sense of justice in society. This is in line with the idea of a progressive type of law enforcement. For this reason, it is suggested that judges and constitutional judges must explore, follow, and understand legal values and a sense of justice that live in society and pay attention to the principles of justice and legal certainty